2016
DOI: 10.3389/fmicb.2016.00607
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of Kanamycin Conjugated Gold Nanoparticles with Potent Antibacterial Activity

Abstract: With a sharp increase in the cases of multi-drug resistant (MDR) bacteria all over the world, there is a huge demand to develop a new generation of antibiotic agents to fight them. As an alternative to the traditional drug discovery route, we have designed an effective antibacterial agent by modifying an existing commercial antibiotic, kanamycin, conjugated on the surface of gold nanoparticles (AuNPs). In this study, we report a single-step synthesis of kanamycin-capped AuNPs (Kan-AuNPs) utilizing the combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 57 publications
(61 reference statements)
1
81
1
1
Order By: Relevance
“…AuNPs were reported to have intrinsic antibacterial activity against various pathogenic microorganism. So, they were intentionally combined with antibiotics for increasing the efficacy of antibacterial activity (Bhattacharya et al, 2012;Kalita et al, 2016;Payne et al, 2016). Researches about developing new antibacterial agents have focused on colloidal gold nanoparticles since they can penetrate through the outer membrane and the peptidoglycan layer of bacteria and result in the production of reactive oxygen species (ROS) (Zhao & Jiang, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AuNPs were reported to have intrinsic antibacterial activity against various pathogenic microorganism. So, they were intentionally combined with antibiotics for increasing the efficacy of antibacterial activity (Bhattacharya et al, 2012;Kalita et al, 2016;Payne et al, 2016). Researches about developing new antibacterial agents have focused on colloidal gold nanoparticles since they can penetrate through the outer membrane and the peptidoglycan layer of bacteria and result in the production of reactive oxygen species (ROS) (Zhao & Jiang, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested in another study that the accumulation of the kanamycin conjugated AuNPs within the bacterial membrane and cytosol occurred by virtue of the facilitation of the antibiotic transportation across the bacterial membrane via the AuNPs. In addition, the local concentration of the antibiotic increased compared to antibiotic alone, which eventually resulted in the cell lysis (Payne et al, 2016). The membrane peptidoglycan layer thickness of Gram-positive bacteria is thick and especially, B. subtilis was reported to be a very resistant bacteria and thus able to endure very harsh conditions (Shamaila et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Another paper reported that the antibacterial mechanism of Au NPs was that these Au NPs accumulated within the bacterial membrane and cytoplasm, and then interacted with the protein synthesis machinery to directly inhibit bacterial growth. 37 Au NPs showed higher activity against Escherichia coli than Staphylococcus aureus. It was the cell wall of the Staphylococcus aureus contains a thick layer of peptidoglycan, forming a more rigid structure leading to difficult penetration of the Au NPs compared to the Escherichia coli.…”
Section: Ftir Analysismentioning
confidence: 95%
“…Au-NPs conjugated with an antibiotic, kanamycin, exhibited dose-dependent broad-spectrum antibacterial activity against both Gram-positive and Gram-negative bacteria, including bacteria resistant to kanamycin. It was indicated that the increased efficacy might have resulted due to the damage of the bacterial cell envelope, consequently resulting in the leakage of intracellular components and cell death (Payne et al, 2016).…”
Section: )mentioning
confidence: 99%